Perceptions of parents and religious leaders regarding minimal invasive tissue sampling to identify the cause of death in stillbirths and neonates: results from a qualitative study - Anam Feroz; Mohsina Noor Ibrahim; Elizabeth M. McClure; Anum Shiraz Ali; Shiyam Sunder Tikmani; Sayyeda Reza; Zahid Abbasi; Jamal Raza; Haleema Yasmin; Khadija Bano; Afia Zafar; Sameen Siddiqi; et al. (BMC, 2019)
Abstract Background Recently, the minimal invasive tissue sampling (MITS) procedure has been developed to support determination of the cause of death as an alternate to conventional autopsy, especially in countries where complete diagnostic autopsy is not routine. To assess the feasibility of implementation of the MITS procedure for a study to determine cause of death in premature births and stillbirths in south Asia, we explored the views and perceptions of parents and religious leaders on the acceptability of MITS. Methods A qualitative study was conducted at the National Institute of Child Health (NICH) hospital of Karachi, Pakistan. Focus group discussions (FGDs) were conducted with parents of newborns who visited well-baby clinics of the NICH hospital for post-natal check-ups. Key-informant interviews (KIIs) were conducted with religious leaders. Data were analyzed using NVivo 10 software. Results A total of 13 interviews (FGDs = 8; KIIs = 5) were conducted. Three overarching themes were identified: (I) acceptability of MITS; (II) concerns affecting the implementation of MITS; and (III) religious and cultural perspectives. Participants' acceptance of MITS was based on personal, religious, cultural and social beliefs. Parents widely recognized the need for this procedure in cases where the couple had experienced multiple stillbirths, neonatal deaths and miscarriages. Counseling of parents was considered vital to address emotional concerns of the parents and the family. Religious leaders indicated acceptability of the MITS procedure from a religious perspective and advised that respect for the deceased and consent of the guardians is mandatory when performing MITS. Conclusions This qualitative study provided a unique opportunity to understand the views of parents and religious leaders towards the use of MITS. Generally, MITS appears to be an acceptable method for identifying the cause of death in neonates and stillbirths, provided that the deceased is respected and buried as soon as possible without any delays and parents are counseled appropriately. Findings from this research are essential in approaching families for consent for MITS.